2019
DOI: 10.1093/ejcts/ezz341
|View full text |Cite
|
Sign up to set email alerts
|

External validity of a model to predict postoperative atrial fibrillation after thoracic surgery

Abstract: OBJECTIVES A prediction model developed by Passman et al. stratifies patients’ risk of postoperative atrial fibrillation (POAF) after major non-cardiac thoracic surgery using 3 simple factors (sex, age and preoperative resting heart rate). The model has neither undergone external validation nor proven to be relevant in current thoracic surgery practice. METHODS A retrospective single-centre analysis of all patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Furthermore, as a marker of the autonomic nervous system, resting heart rate was associated with incident AF, 12,13 which played an important role in the pathological mechanism of AF 31,32 . A predictive model for POAF constituted by three simple parameters, including resting heart rate, showed well efficacy in both internal and external validation cohorts 9,10 . However, the predictive value of resting heart rate for POAF after PTE has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as a marker of the autonomic nervous system, resting heart rate was associated with incident AF, 12,13 which played an important role in the pathological mechanism of AF 31,32 . A predictive model for POAF constituted by three simple parameters, including resting heart rate, showed well efficacy in both internal and external validation cohorts 9,10 . However, the predictive value of resting heart rate for POAF after PTE has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors, including age, male sex, and previous history of AAs, have been reported to be associated with AA after PTE 7 . It is well known that the resting heart rate is also a risk factor for POAF 9,10 . However, its role in predicting POAF after PTE has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This study is also the first to trial the concept of individualized prophylactic therapy targeted to high-risk individuals. We can identify individuals with a 4-fold increase of POAF who account for 51% of POAF cases using three simple factors available preoperatively [17]. Giving prophylactic amiodarone to only those high-risk individuals demonstrates an opportunity to optimize the benefits of prophylactic amiodarone and avoid unnecessary harm in individuals with low probability of developing POAF.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the literature for risk stratification tools to predict POAF after thoracic surgery, we only identified one which was internally validated for all patients undergoing major thoracic surgery and contained factors obtainable in the preoperative period (resting heart rate, gender, and age) [4,15,16]. After evaluation of this tool at our institution in a sample of 2036 patients undergoing major thoracic surgery between 2008 and 2018, we found it to also be externally valid [17]. To facilitate identifying potential candidates for prophylaxis, we translated this POAF risk model into a designation of high vs low risk.…”
Section: Prediction Of Poafmentioning
confidence: 99%
“…For example, several studies investigating postoperative complications of MIE grouped POAF with other cardiovascular complications together [11][12][13]. Other studies evaluating POAF risk as a single outcome yielded inconsistent results [14][15][16][17]: while one study reported decreased POAF risk after MIE [18], other studies did not find any association between MIE and POAF [16,19]. Another gap in the literature is the lack of consistent short-term mortality rate data after MIE.…”
Section: Introductionmentioning
confidence: 99%